The Influence of Employee Information System, Employee Competence and Person-Jobfit on the Performance of XYZ Health Center Employees with Job Satisfaction as a Mediation Variable - Asmara, Erlysa; Fauzia, Ika Yunia (LP2M IAIN Palopo, 2025)
This study aims to analyze the effect of employee information systems, employee competence, and person-job fit on the performance of XYZ Puskesmas employees, with job satisfaction as an intervening variable. This research uses a quantitative approach with a survey method and data collection through questionnaires distributed to XYZ Health Center employees. Data analysis was carried out using the Structural Equation Modeling (SEM) method with the help of SmartPLS software. The results showed that employee information systems, employee competence, and person-job fit had a positive and significant effect on job satisfaction. In addition, job satisfaction is proven to have a positive and significant influence on employee performance. These findings indicate that improving good information systems, increasing competence, and job placement in accordance with individual abilities will increase job satisfaction, which in turn has an impact on improving overall employee performance.